Nepal : Can Information and Cash Improve Children's Development - World Bank (Washington, DC, 2017)
In Nepal, researchers supported by the World Bank's Strategic Impact Evaluation Fund worked with the government to develop a program to inform pregnant women and mothers of young children on how to best care for themselves and their children, using already ongoing community meetings to deliver messages. An impact evaluation was designed to measure the effectiveness of the information and to test whether combining this with a short-term cash transfer for mothers made it more effective. The evaluation found that mothers who received both information and cash reported a higher likelihood of breastfeeding their babies and reported that they took recommended vitamins and their households consumed more calories. Also, their children had better fine and gross motor skills as compared to the control group, which didn't receive this intervention. But there weren't any reductions in malnutrition. Two years later, after a devastating earthquake in 2015, researchers returned and found that while mothers still retained more knowledge on good nutrition practices, their children didn't show any continued development gains. The results are helping the Government of Nepal as it considers new steps for improving child development, and the materials used during the meetings to inform women about healthy nutrition have been adopted for wider use.